2015
DOI: 10.1371/journal.pone.0121997
|View full text |Cite
|
Sign up to set email alerts
|

Iron Metallodrugs: Stability, Redox Activity and Toxicity against Artemia salina

Abstract: Iron metallodrugs comprise mineral supplements, anti-hypertensive agents and, more recently, magnetic nanomaterials, with both therapeutic and diagnostic roles. As biologically-active metal compounds, concern has been raised regarding the impact of these compounds when emitted to the environment and associated ecotoxicological effects for the fauna. In this work we assessed the relative stability of several iron compounds (supplements based on glucoheptonate, dextran or glycinate, as well as 3,5,5-trimethylhex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 33 publications
(44 reference statements)
1
15
0
4
Order By: Relevance
“…Studies with mollusks in Cd contaminated regions reveal an increase of MT in the cytosol of gill cells, acting as an important stress marker 14 . Another stress marker of environmental pollution is lipid peroxidation (LPO), also associated with excess of metals [15][16][17][18] . Several studies with vertebrates and invertebrates showed that with rising pollution levels (particularly with respect to cadmium), there is an increase in the antioxidant systems, including LPO 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies with mollusks in Cd contaminated regions reveal an increase of MT in the cytosol of gill cells, acting as an important stress marker 14 . Another stress marker of environmental pollution is lipid peroxidation (LPO), also associated with excess of metals [15][16][17][18] . Several studies with vertebrates and invertebrates showed that with rising pollution levels (particularly with respect to cadmium), there is an increase in the antioxidant systems, including LPO 19 .…”
Section: Discussionmentioning
confidence: 99%
“…A síntese da sonda Fl-aTf foi usando métodos já descritos 187,190,181 . A desferrioxamina tem maior afinidade pelo ferro do que a transferrina, no entanto a cinética dessa reação é muito lenta, pois na proteína, o ferro encontra-se ligado em um compartimento afastado da superfície da molécula.…”
Section: 22teste Com Apotransferrina Fluorescente (Fl-atf)unclassified
“…A lisina foi utilizado para se combinar com o excesso das moléculas do 5-DTAF que não reagiram com a proteína. A purificação da Fl-a-tf foi feita por diálise por 12 h a 4°C frente ao citrato (pH da reação 5,5), metodologia comumente aplicada a compostos com altas massas moleculares (neste caso, > 10 kDa) 187,190 …”
Section: Avaliação Da Capacidade Quelante Dos Mtdfounclassified
“…Derivados 183 , podendo ser usado como fárma-co para repor ferro em sistemas localizados, aproveitando as propriedades lipossolúveis que apresentam 154 . Por outro lado, a última década testemunhou interesse de pesquisa renovado em compostos organometálicos anticancerígenos 301,302 .…”
Section: Estudo Da Estabilidade Dos Derivados De Ferrocenounclassified
“…Várias rotas têm sido propostas para o transporte de metais através da membrana citoplasmática, sendo elas: (i) transporte iônico mediado por ligação do metal à membrana; uma vez no citosol, o metal se liga a proteínas e então é continuadamente transportado de forma passiva na célula, fazendo com que o metal se torne, consequentemente, indisponível para retornar ao meio externo 41 ; (ii) transporte através de canais de proteínas onde os íons de metal são transportados por gradiente hidrofílico; (iii) difusão passiva do metal na bicamada lipídica dissolvida; e, (iv) endocitose -englobamento de partículas ferro-metálicas as quais são transferidas para vesículas intracelulares. Essas duas últimas rotas são, provavelmente, as de menor importância para a absorção típica de metais da solução pelos crustáceos aquáticos [42][43][44] .…”
unclassified